Biocontrol efficacy and possible mechanism of a broad-spectrum antagonistic yeast, Pichia kluyveri NY23, screened from peach fruit via microbiome analysis - Mengyang Xing; Qiu Long; Keyan Zhao; Yong Chen; Shiping Tian; Boqiang Li (Postharvest Biology and Technology, 2027)

Fires reshape species-specific drought resilience of typical conifers in southwestern China - Peiyao Tao; Fen Zhang; Tian Chen; Xinglin Huang; Feifei Zhou; Keyan Fang; Xiaohua Gou; Yifei Zhao (Forest Ecology and Management, 2026)

Fine-grained hierarchical crop type classification from integrated hyperspectral EnMAP data and multispectral sentinel-2 time series: A large-scale dataset and dual-stream transformer method - Wenyuan Li; Shunlin Liang; Yuxiang Zhang; Liqin Liu; Keyan Chen; Yongzhe Chen; Han Ma; Jianglei Xu; Yichuan Ma; Shikang Guan; Zhenwei Shi (Remote Sensing of Environment, 2026)

Regulatory effects of Annulohypoxylon stygium metabolites on the dimorphic transition of Tremella fuciformis - Haichen Huang; Lingli Wei; Jialan Zheng; Shuyu Xing; Yingqi Tang; Silong Chen; Keyan Shen; Jianqiu Chen; Shujing Sun (Food Bioscience, 2026)

Morphological regulation of a flower-like hollow β-cyclodextrin covalent organic frameworks for enhanced hydrophilicity and chiral separation - Liqin Cao; Mengxue Tang; Keyan Chen; Qixuan Mu; Ruijun Li; Yibing Ji (Analytica Chimica Acta, 2026)

Orbitally driven sea surface temperature changes during the mid- to late Holocene: A global picture - Zanchenling Wang; Baoqi Huang; Jianghui Du; Keyan Fang; Xiaosong Chen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Toxic effects of 5-hydroxymethylfurfural on intestinal epithelial cell and its impact on the expression of MAPK pathway-related genes - Dongying Qin; Xunlin Chen; Keyan Pan; Zixuan Tang; Zhongzheng Chen; Xiaorong Lin; Yuanyuan Zhang (Food and Chemical Toxicology, 2026)

Interdecadal winter temperature variability driven by the East China Sea Mode: A global perspective - Keyan Fang; Hao Wu; Shuheng Lin; Jun Cheng; Jane Liu; Deliang Chen; Jinbao Li; Cesar Azorin-Molina; Zheng Zhao; Frode Stordal; Shuo Hao; Nicole Davi; et al. (Science China Earth Sciences, 2026)

Microbial adaptation and environmental co-selection drive antimicrobial resistance risk in agricultural ditches, evidence from the multilevel ditch-river continuum - Xiangyao Wu; Yulin Qi; Lingchen Meng; Keyan Li; Chao Ma; Dietrich A. Volmer; Chunmei Chen; Peizhe Sun; Pingqing Fu; Zhifeng Yan (Journal of Hazardous Materials, 2026)

Poly(amidoamine) dendrimer-loaded grape polyphenols suppress DPP4-mediated adipogenesis and inflammation to alleviate obesity-associated osteoarthritis - Jingting Zhang; Di Zhang; Keyan Chen; Fu Chen (Chemical Engineering Journal, 2026)

Identification of new virulence factors in Penicillium expansum via comparative transcriptomic analysis of three Penicillium species - Ting Liu; Keyan Zhao; Mengyang Xing; Yong Chen; Shiping Tian; Boqiang Li (Postharvest Biology and Technology, 2026)

Iterative indicator kriging using probability and pseudo-information entropy drop for spatial distribution estimation of geological discrete variables - Guangjun Ji; Zizhao Cai; Yan Lu; Qian Wang; Jianguo Chen; Keyan Xiao (Engineering Geology, 2026)

Menopause status and modifiable risk factors for early menopause in China: a nationwide cross-sectional study on geographical disparities - Ting Guo; Xinyi Wu; Peihao Liu; Zifeng Cao; Keyan Xu; Li Yang; Guangmei Huang; Qianqian Ma; Xiaomin Yang; Xin Gao; Yehuan Yang; Yilin Yang; et al. (Science Bulletin, 2026)

GTF: A New Interpretable Graph Neural Network for Geochemical Anomaly Detection in Mineral Prospectivity Mapping - Zhengbo Yu; Binbin Li; Fan Zhang; Jiangwei You; Baizhi Li; Zhe Chen; Shuai Zhang; Keyan Xiao (Natural Resources Research, 2026)

AgriFM: A multi-source temporal remote sensing foundation model for Agriculture mapping - Wenyuan Li; Shunlin Liang; Keyan Chen; Yongzhe Chen; Han Ma; Jianglei Xu; Yichuan Ma; Yuxiang Zhang; Shikang Guan; Husheng Fang; Zhenwei Shi (Remote Sensing of Environment, 2026)

Single-tube duplex isothermal amplification assay for rapid detection of pistachio and cashew allergens - Ruifeng Mao; Yuwen Zhou; Xinru Zhan; Miqi Tan; Yue Sun; Yuanmeng Dong; Keyan Yuan; Yingying Chen; Wei Wang; Dengchao Li; Enjie Diao (Food Control, 2026)

Lipase-based HKUST-1 (Cu) biocomposites as chiral stationary phase for enantiomer separation in capillary electrochromatography - Mengxue Tang; Jiale Zhang; Qixuan Mu; Keyan Chen; Yibing Ji (Analytica Chimica Acta, 2026)

Drip irrigation combined with organic fertilizers improves crop N uptake and yield by reducing soil salinity and N loss in saline–alkali sunflower farmlands - Min Hu; Yue Li; Zhijun Chen; Keyan Lv; Yunwu Xiong; Guanhua Huang (Soil and Tillage Research, 2026)

Multi-sensor multi-dimensional data fusion method for submarine cable anchor damage event identification - Chunying Xu; Xinjie Wu; Jingqi Fang; Jianrong Chen; Keyan Xiao; Jiawang Chen; Chuliang Wei; Hailun Fu (Ocean Engineering, 2025)

Tree-ring indicators of near-surface wind speed in the Poyang Lake area of monsoonal China - Min Zhou; Keyan Fang; Maowei Bai; Feifei Zhou; Yao Chen; Di Zhang; Wanru Tang; Zepeng Mei; Cesar Azorin-Molina (Dendrochronologia, 2025)

In Vitro Characterization and Identification of Potential Probiotic Yeasts Isolated from Zaopocu, a Traditional Fermented Dregs Vinegar from Hainan Island - Lin Huang; Yuan Wang; Keyan Zhong; Ziyuan Jiang; Hengkai Jia; Shuying Chen; Zhiyuan Zhao; Xinjun Chen (Probiotics and Antimicrobial Proteins, 2025)

Exploring pentagonal PdPTe and PdTe2 monolayers as potential in strain sensors, photodiode and gas sensors applications - Keyan Han; Chenyu Tao; Peng Tang; Zejiang Peng; Xianbo Xiao; Tong Chen (Chemical Engineering Journal, 2025)

Organic amendments promote sunflower nutrient uptake by recruiting stable beneficial microbiomes in saline–alkali farmland - Min Hu; Yue Li; Zhijun Chen; Keyan Lv; Yunwu Xiong; Guanhua Huang (Plant and Soil, 2025)

Sterol-modified plants reduce aphid performance by limiting sterol availability - Ivy W. Chen; Jiaxin Lei; Zekun Jin; Adriana E. Alvarez; Robert J. Grebenok; Stephen Fletcher; Spencer T. Behmer; Keyan Zhu-Salzman (Insect Biochemistry and Molecular Biology, 2025)

Targeting ferroptosis in pemphigus vulgaris using aptamer-modified extracellular vesicles - Yishu Tang; Yuxuan Zhang; Hongli Ding; Hao Jin; Liang Zhang; Mao Luo; Keyan Chen; Bin Wei (Chemical Engineering Journal, 2025)

Associations of long-term exposure to fine particulate matter and its components with ovarian aging: Evidence from a cross-sectional study in China - Zifeng Cao; Xinyi Wu; Hongyuan Liu; Keyan Xu; Yehuan Yang; Manting Yang; Daimin Wei; Shidou Zhao; Xue Jiao; Qi Zhao; Ruimin Zheng; Yingying Qin; et al. (Journal of Hazardous Materials, 2025)

The first temperature reconstruction based on tree-ring blue intensity in the Qinling Mountains - Mei Xie; Qiufang Cai; Yu Liu; Keyan Fang; Qiuyue Zhou; Meng Ren; Kebayier Meng; Qiang Li; Changfeng Sun; Huiming Song; Dan Chen; Yufei Chen (Dendrochronologia, 2025)

Ferroelectric-coupled MXene/BaTiO3 nanocomposite empowering flexible triboelectric nanogenerators for deep learning-enhanced human-machine health monitoring - Haoyu Yuan; Ziran Wang; Keyan Yuan; Ke Li; Chen Wang; Luyang Zhang; Zaiyu Zhang; Chaqi Gai; Chengpeng Zhang; Guoliang Lu; Zhongjing Ren; Haipeng Wang; et al. (Chemical Engineering Journal, 2025)

Life cycle greenhouse gas emission of pork production in China: Carbon inequality embodied in supply chain - Shuru Chen; Keyan Chen; Fan Wu; Jing You (Resources, Conservation and Recycling, 2025)

The biodegradation pathway of HBCDs in the enriched microbial community - Bing Zhang; Wenqi Luo; Yongjin Liu; Haonan Chen; Tiantian Pan; Baole Wang; Keyan Li; Huaqing Jia; Shirou Zhou; Shanshan Meng; Xueying Ye; Tao Peng; et al. (International Biodeterioration & Biodegradation, 2025)

Silibinin’s role in counteracting neuronal apoptosis and synaptic dysfunction in Alzheimer’s disease models - Baohui Zhang; Di Zhang; Keyan Chen; Tengfei Wu (Apoptosis, 2025)

A scalable photovoltaic-type photoelectrotrophic denitrification reactor for selective conversion nitrate to nitrogen via isolating reactive oxygen species - Man Chen; Keyan Chen; Yang Li; Youming Diao; Yixi Li; Raymond Jianxiong Zeng; Shungui Zhou (Chemical Engineering Journal, 2025)

Recent progress of Clostridium butyricum in fish culture: Maintenance of intestinal homeostasis, improvement of disease resistance, activation of immune signaling pathways, and positive effects on fish - Keyan Cai; Jingyi Chen; Zhepeng Zhang; Yawen Ye; Shangyuan Sang; Xiaohu Luo; Yajun Wang; Kai Shan; Changrong Ou; Ling-ling Jia (Aquaculture, 2025)

Addressing the plastisphere: Sustainable approaches to combat plastic pollution - Wei Xuyang; Khalida Khalil; Tian Zhuo; Chen Keyan; Mohamed Yusuf Mohamed Nazir; Wan Syaidatul Aqma; Niu Qiu Hong (Science of The Total Environment, 2025)

An Elevated Influence of the Low‐Latitude Drivers on the East Asian Winter Monsoon After Around 1990 - Bozhou Chen; Keyan Fang; Zepeng Mei; Tinghai Ou; Feifei Zhou; Hao Wu; Zheng Zhao; Deliang Chen (International Journal of Climatology, 2024)
Current East Asian winter monsoon (EAWM) indices effectively depict the associated high‐ and low‐latitude atmospheric circulations. However, the spatial dynamics of the winter coldness within the monsoon domain are not well adequately represented by EAWM indices. We introduce a novel approach to classify winter temperatures based on both their co‐variability and their mean values. We classified the EAWM domain into three distinct modes: northern (ranging from −27°C to −15°C), central (−14°C to 5°C), and southern (6°C to 27°C). The northern mode, characterised by intense coldness, correlates with a strengthened westerlies that traps Arctic cold air masses during the positive phase of the Arctic Oscillation (AO). In contrast, the southern mode is primarily influenced by low‐latitude oceanic and atmospheric patterns, particularly for near‐coast areas. The central mode, representing an interplay of both high and low‐latitude processes, encapsulates the comprehensive characteristics of the EAWM. Our analysis reveals a notable shift in the relationships among the northern, central, and southern modes around 1990. Prior to this year, the EAWM was predominantly influenced by northern atmospheric patterns, while there is a discernible increase in the influence of low‐latitude drivers afterwards. This shift may be linked to the significant warming in the western Pacific and Indian Oceans, underscoring the heightened role of low‐latitude drivers on the EAWM.

A comprehensive physiological and -Omic analysis of trypsin-mediated protection of green pepper fruits from chilling injury - Keyan Zhao; Xuanqi Wang; Xiaozhen Yue; Jieyu Lv; Xiaodi Xu; Hongshan Lu; Jinhua Zuo; Xiangbin Xu; Bin Chen; Shuzhi Yuan; Qing Wang (Food Chemistry, 2024)

Deciphering the transfer of hydroclimate signals to tree-ring δ18O using a proxy system model in East Asia's Meiyu region - Yesi Zhao; Huayu Lu; Keyan Fang; Peng Zhang; Deliang Chen; Achim Bräuning; Jussi Grießinger; Bao Yang; Chenghong Liang; Hongyan Zhang; Yiqian Sun; Qing Jin; et al. (Chemical Geology, 2024)

Deleterious variants in RNF111 impair female fertility and induce premature ovarian insufficiency in humans and mice - Chengcheng Song; Yingying Qin; Yan Li; Bingyi Yang; Ting Guo; Wenqing Ma; Dian Xu; Keyan Xu; Fangfang Fu; Li Jin; Yanhua Wu; Shuyan Tang; et al. (Science China Life Sciences, 2024)

Deep multimodal fusion for 3D mineral prospectivity modeling: Integration of geological models and simulation data via canonical-correlated joint fusion networks - Yang Zheng; Hao Deng; Jingjie Wu; Shaofeng Xie; Xinyue Li; Yudong Chen; Nan Li; Keyan Xiao; Norbert Pfeifer; Xiancheng Mao (Computers & Geosciences, 2024)

Identification of Geochemical Anomalies Using an End-to-End Transformer - Shuyan Yu; Hao Deng; Zhankun Liu; Jin Chen; Keyan Xiao; Xiancheng Mao (Natural Resources Research, 2024)

Modulations of NAO on the interplay between monsoon and westerlies in Asia on interdecadal timescales - Qichao Yao; Ben Zheng; Keyan Fang; Amy Hudson; Feifei Zhou; Haonan Chen; Haiming Tan; Futao Guo; Valerie Trouet (Climate Dynamics, 2024)

Summer heat induced the decline of Pinus taiwanensis forests at its southern limit in humid Subtropical China - Feifei Zhou; Zhipeng Dong; Keyan Fang; Dongliang Cheng; Hui Tang; Tinghai Ou; Fen Zhang; Deliang Chen (Agricultural and Forest Meteorology, 2024)

Importance of forest stand structures for gross rainfall partitioning on China’s Loess Plateau - Xu Hu; Zhaoqi Fu; Ge Sun; Biao Wang; Keyan Liu; Churui Zhang; Lu Han; Lixin Chen; Zhiqiang Zhang (Journal of Hydrology, 2024)

RNAi-mediated plant sterol modification to control insect herbivore pests: insights from Arabidopsis and the diamondback moth - Ivy W. Chen; Robert J. Grebenok; Cheng Zhao; Li He; Jiaxin Lei; Rui Ji; Nicolo Hernandez; Joshua S. Yuan; Hisashi Koiwa; Spencer T. Behmer; Keyan Zhu-Salzman (Journal of Pest Science, 2024)

Comparing multiple machine learning models to investigate the relationship between urban morphology and PM2.5 based on mobile monitoring - Jianfeng Zhang; Yang Wan; Meng Tian; Hao Li; Keyan Chen; Xuesong Xu; Lei Yuan (Building and Environment, 2024)

Investigation on the anisotropy of meso-mechanical properties of shale rock using micro-indentation - Tianshou Ma; Keyan Liu; Xue Su; Ping Chen; P. G. Ranjith; Dmitriy A. Martyushev (Bulletin of Engineering Geology and the Environment, 2024)

Drought variations in the southeastern Tibetan Plateau region since 1704 and their link to the Atlantic Multidecadal Oscillation - Wanru Tang; Keyan Fang; Zepeng Mei; Feifei Zhou; Hao Wu; Kristina Seftigen; Xinguang Cao; Zhipeng Dong; Maowei Bai; Yao Chen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Quantification of soil erosion dynamics in the hilly red soil region of Southeast China based on exposed roots - Di Zhang; Feifei Zhou; Keyan Fang; Nicole Davi; Zhibiao Chen; Fei Wang; Yao Chen (CATENA, 2023)

Evaluating the seasonal effects of building form and street view indicators on street-level land surface temperature using random forest regression - Keyan Chen; Meng Tian; Jianfeng Zhang; Xuesong Xu; Lei Yuan (Building and Environment, 2023)

Weakened western Pacific teleconnection pattern caused a decrease in spring persistent rainfall in north of 26°N over Southeast China - Yao Chen; Chongqing Wang; Feifei Zhou; Shixiong Jiang; Xi Li; Sunxian Weng; Xinyuan Wan; Rongyang Xiao; Qiang Liu; Keyan Fang (International Journal of Climatology, 2023)
The spring persistent rainfall (SPR) is a unique synoptic and climatic phenomenon before the onset of the Asian summer monsoon over Southeast China (SEC). The warming climate has caused notable interdecadal changes of various climate systems, such as the Asian summer monsoon. However, it is still unclear whether there is a regime shift within the SPR band. To fill this knowledge gap, the boreal spring (March–May) rainfall data across SEC from the Climate Research Unit TS 4.05 are used herein to reveal its spatio‐temporal variations for 1951–2019 with the empirical orthogonal function (EOF) analysis. The EOF1 pattern exhibits a spatial monotonic variability of the SPR over SEC, which is jointly impacted by the El Niño‐Southern Oscillation and the Arctic Oscillation. The EOF2 pattern, a south–north dipole pattern, highlights a marked decrease (increase) of the SPR approximately to north (south) of the 26°N. We find that the decrease in the northern SPR band is closely modulated by western Pacific teleconnection pattern (WPP). Recent weakening WPP is coincident with a decline of the East Asian subtropical jet over this area, causing anomalous descending motions and thus accounts for persistent decline of the SPR over north of 26°N.

Reconstructed Jing River streamflow from western China: A 399-year perspective for hydrological changes in the Loess Plateau - Xiaoen Zhao; Keyan Fang; Feng Chen; Hadad Martín; Fidel A. Roig (Journal of Hydrology, 2023)

Exploring the fungal communities and their correlation with the physicochemical properties of Zaopocu, a distinctive fermented food on Hainan island - Lin Huang; Yalin Han; Keyan Zhong; Xinjun Chen (Biologia, 2023)

Mapping and identification of CsSF4, a gene encoding a UDP-N-acetyl glucosamine-peptide N-acetylglucosaminyltransferase required for fruit elongation in cucumber (Cucumis sativus L.) - Keyan Zhang; Danqing Yao; Yue Chen; Haifan Wen; Jian Pan; Tingting Xiao; Duo Lv; Huanle He; Junsong Pan; Run Cai; Gang Wang (Theoretical and Applied Genetics, 2023)

Improved spring temperature reconstruction using earlywood blue intensity in southeastern China - Xinguang Cao; Hongbing Hu; Pei‐ken Kao; Brendan M. Buckley; Zhipeng Dong; Xiuling Chen; Feifei Zhou; Keyan Fang (International Journal of Climatology, 2022)
Because instrumental observations are too short to fully represent long‐term natural variability, high‐resolution temperature proxy records are essential to understanding past climate and assessing current climate variability in the context of long‐term patterns. In the subtropics, progress in this field has been hampered by a relative lack of long and truly temperature‐sensitive proxy records. In this study, we provide an assessment of the dendroclimatic potential of blue intensity (BI) and ring‐width (RW) measurements from two hot/humid Pinus massoniana sites in China. Our results show that RW exhibits a significant ( p

An Improved GWR Approach for Exploring the Anisotropic Influence of Ore-Controlling Factors on Mineralization in 3D Space - Jixian Huang; Xiancheng Mao; Hao Deng; Zhankun Liu; Jin Chen; Keyan Xiao (Natural Resources Research, 2022)

Mineral Prospectivity Mapping based on Isolation Forest and Random Forest: Implication for the Existence of Spatial Signature of Mineralization in Outliers - Shuai Zhang; Emmanuel John M. Carranza; Keyan Xiao; Hantao Wei; Fan Yang; Zhenghui Chen; Nan Li; Jie Xiang (Natural Resources Research, 2022)

Priming of rice defense against a sap-sucking insect pest brown planthopper by silicon - Yibin Lin; Xianhui Lin; Chaohui Ding; Ming Xia; Rongrong Xue; Zhongxiang Sun; Daoqian Chen; Keyan Zhu-Salzman; Rensen Zeng; Yuanyuan Song (Journal of Pest Science, 2022)

CsUFO is involved in the formation of flowers and tendrils in cucumber - Yue Chen; Haifan Wen; Jian Pan; Hui Du; Keyan Zhang; Leyu Zhang; Yao Yu; Huanle He; Run Cai; Junsong Pan; Gang Wang (Theoretical and Applied Genetics, 2021)

Geochemically Constrained Prospectivity Mapping Aided by Unsupervised Cluster Analysis - Shuai Zhang; Emmanuel John M. Carranza; Keyan Xiao; Zhenghui Chen; Nan Li; Hantao Wei; Jie Xiang; Li Sun; Yang Xu (Natural Resources Research, 2021)

Mapping and identification of CsSh5.1, a gene encoding a xyloglucan galactosyltransferase required for hypocotyl elongation in cucumber (Cucumis sativus L.) - Keyan Zhang; Junsong Pan; Yue Chen; Ying Wei; Hui Du; Jingxian Sun; Duo Lv; Haifan Wen; Huanle He; Gang Wang; Run Cai (Theoretical and Applied Genetics, 2021)

Co-varying temperatures at 200 hPa over the Earth’s three poles - Keyan Fang; Peng Zhang; Jingming Chen; Deliang Chen (Science China Earth Sciences, 2021)

Electron beam irradiation induces DNA endoreplication in holometabolous juvenile insects: a rapid flow cytometry-based diagnosis - Jiaxin Lei; Ivy W. Chen; Gus Wright; Suresh Pillai; Keyan Zhu-Salzman (Journal of Pest Science, 2020)

Biodegradable chitosan-ethylene glycol hydrogel effectively adsorbs nitrate in water - Changhong Chen; Yiwei Guo; Li Long; Keyan Chen; Xiaolan Hu; Yingwen Xue (Environmental Science and Pollution Research, 2020)

3D Mineral Prospectivity Mapping with Random Forests: A Case Study of Tongling, Anhui, China - Jie Xiang; Keyan Xiao; Emmanuel John M. Carranza; Jianping Chen; Shi Li (Natural Resources Research, 2020)

Responses of the radial growth of the endangered species Keteleeria fortunei to climate change in southeastern China - Zheng Zhao; Keyan Fang; Chunfu Cao; Dai Chen; Xiaoyue Liang; Zhipeng Dong; Peng Zhang (Trees, 2019)

3D Geological Modeling for Mineral System Approach to GIS-Based Prospectivity Analysis: Case Study of an MVT Pb–Zn Deposit - Nan Li; Xianglong Song; Cangbai Li; Keyan Xiao; Shengmiao Li; Haiyan Chen (Natural Resources Research, 2019)

Regeneration of Fe II /Fe III complex from NO chelating absorption by microbial fuel cell - Qiang Liu; Keyan Yu; Peng Yi; Weimin Cao; Xueping Chen; Xiaolei Zhang (Environmental Science and Pollution Research, 2019)

Interdecadal modulation of the Atlantic Multi-decadal Oscillation (AMO) on southwest China’s temperature over the past 250 years - Keyan Fang; Zhengtang Guo; Deliang Chen; Lei Wang; Zhipeng Dong; Feifei Zhou; Yan Zhao; Jinbao Li; Yingjun Li; Xinguang Cao (Climate Dynamics, 2019)

An interdecadal climate dipole between Northeast Asia and Antarctica over the past five centuries - Keyan Fang; Deliang Chen; Zhengtang Guo; Yan Zhao; David Frank; Maosheng He; Feifei Zhou; Feng Shi; Heikki Seppä; Peng Zhang; Raphael Neukom (Climate Dynamics, 2019)

Intensified variability of the El Niño–Southern Oscillation enhances its modulations on tree growths in southeastern China over the past 218 years - Lei Wang; Keyan Fang; Dai Chen; Zhipeng Dong; Feifei Zhou; Yingjun Li; Peng Zhang; Tinghai Ou; Guoyang Guo; Xinguang Cao; Mingtong Yu (International Journal of Climatology, 2018)
Lack of long‐term tree‐ring records in the core regions of the Asian summer monsoon in southeastern China limits our ability of evaluating the current climate change in a historical context. In this study, we developed the first 218‐year tree‐ring chronology (1798–2015) of Pinus massoniana in Zhangping area, Fujian Province, humid subtropical China. This chronology is positively correlated with winter–spring (January–March) temperature ( r = 0.359, p r = 0.351, p r = 0.30, N = 66) matches closely with the ENSO variability during 1950–2015. The modulations of the ENSO on regional tree growth have been the most conspicuous since the 1950s, which corresponds to its enhanced inter‐annual variability. The extreme growth anomalies match quite well with the extreme years of the moisture‐sensitive chronologies. The dry epoch from 1935 to 1958 is the most severe long‐lasting drought in our tree rings, which is a widely distributed pattern in southeastern China and is likely modulated by the La Niña‐like modes in that period.

Drought variation of western Chinese Loess Plateau since 1568 and its linkages with droughts in western North America - Keyan Fang; Zhengtang Guo; Deliang Chen; Hans W. Linderholm; Jinbao Li; Feifei Zhou; Guoyang Guo; Zhipeng Dong; Yingjun Li (Climate Dynamics, 2017)

Nonlinear characteristics of hydroclimate variability in the mid-latitude Asia over the past seven centuries - Feifei Zhou; Keyan Fang; Yingjun Li; Qiuyan Chen; Dan Chen (Theoretical and Applied Climatology, 2016)

Response of Pinus taiwanensis growth to climate changes at its southern limit of Daiyun Mountain, mainland China Fujian Province - Dan Chen; KeYan Fang; YingJun Li; ZhiPeng Dong; Yu Zhang; FeiFei Zhou (Science China Earth Sciences, 2016)

Interdecadal hydroclimate teleconnections between Asia and North America over the past 600 years - Keyan Fang; Heikki Seppä; Deliang Chen (Climate Dynamics, 2015)

Spatiotemporal variability of tree growth and its association with climate over Northwest China - Keyan Fang; Xiaohua Gou; Fahu Chen; Edward Cook; Jinbao Li; Yingjun Li (Trees, 2012)

Precipitation variability during the past 400 years in the Xiaolong Mountain (central China) inferred from tree rings - Keyan Fang; Xiaohua Gou; Fahu Chen; David Frank; Changzhi Liu; Jinbao Li; Miklos Kazmer (Climate Dynamics, 2012)

Tree growth and time-varying climate response along altitudinal transects in central China - Keyan Fang; Xiaohua Gou; Fahu Chen; Jinbao Li; Rosanne D’Arrigo; Edward Cook; Tao Yang; Wenhuo Liu; Fen Zhang (European Journal of Forest Research, 2010)

Spatial drought reconstructions for central High Asia based on tree rings - Keyan Fang; Nicole Davi; Xiaohua Gou; Fahu Chen; Edward Cook; Jinbao Li; Rosanne D’Arrigo (Climate Dynamics, 2010)

Reconstructed droughts for the southeastern Tibetan Plateau over the past 568 years and its linkages to the Pacific and Atlantic Ocean climate variability - Keyan Fang; Xiaohua Gou; Fahu Chen; Jinbao Li; Rosanne D’Arrigo; Edward Cook; Tao Yang; Nicole Davi (Climate Dynamics, 2010)

Tree‐ring based drought reconstruction for the Guiqing Mountain (China): linkages to the Indian and Pacific Oceans - Keyan Fang; Xiaohua Gou; Fahu Chen; Rosanne D'Arrigo; Jinbao Li (International Journal of Climatology, 2010)
We have reconstructed the Palmer Drought Severity Index (PDSI) from 1618 to 2005 for the Guiqing Mountain area, north central China, using tree rings of Pinus tabulaeformis . The reconstruction explains 49% of the actual PDSI variance during the common period 1951–2005. The PDSI reconstruction is representative of moisture conditions over a large area to the south and east of the sampling site, the core area for the 1997 severe drought. It shows slightly different variations when compared to other available PDSI reconstructions north and west of the sampling sites. The drought epoch since 1994 is most severe for our study region, with least intensity for the Helan Mountain area. The drought in 1997 was centered in the Guiqing Mountain area, and appears to be the most extreme drought event over the length of reconstruction. Significant spectral peaks are identified at 2.1, 2.3, 2.5, 3.2, 3.6, 42.7 and 53.8 years. Our reconstructed droughts are significantly correlated with sea surface temperature in the northern Indian Ocean, western equatorial Pacific Ocean, eastern equatorial Pacific Ocean, Eastern China Sea and Sea of Japan. The linkages to the Indian and Pacific Oceans suggest the connection of regional moisture variations to the Asian monsoon circulations. Copyright © 2009 Royal Meteorological Society

Response of regional tree-line forests to climate change: evidence from the northeastern Tibetan Plateau - Keyan Fang; Xiaohua Gou; Fahu Chen; Jianfeng Peng; Rosanne D’Arrigo; William Wright; Mai-He Li (Trees, 2009)